Penyuluhan Mengenai Dagusibu (Dapatkan, Gunakan, Simpan, Dan Buang) Obat dengan Benar Di Desa Kandangmukti, Kecamatan Leles, Kabupaten Garut - Alamsyah, Femi Fauziah; Elminar, Sepia; Azzahro, Sana Fathimah; Abiyyi, Nazdifa; Nurwahyudin, Nanda Malika; Gumilar, Muhammad Andri; Fatin Akuan, Drianita Nisrina; Nurwati, Bunga Alfitria; Yansen, Arjuna Haimi; Sabilana, Arina; Arzasana, Tiasaria Hazimah (Yayasan Cendekia Gagayunan Indonesia, 2025)
This work program aims to increase knowledge and raise community awareness about the importance management and supervision of mediacition usage. In crayying out this program, we proper management and suoervision of medivation usage, In carraying out this program, we involed 16 member of the Family Empowerent and Walfare Organization (PKK) as the target for education on the over-the-counter medications commonly kept at home as a means pf self-treatment without medical asistence. The implementation of the activity was divided into three parts: the first part was the introduction, the second part involved a direct presentation of the material, and the third part was the closing, which included a Q&A session and discussion. The result of this activity showed an improvement in the community’s knowledge, understing, and awareness regarding the proper ways to obtain, use, and dispose of medication. In conclusion, the DAGUSIBU health seminar successfully had positive impact on improving the safety of medication use in the community.